Transcriptomic basis for reinforcement of elm antiherbivore defence mediated by insect egg deposition. Issue 23 (22nd November 2018) - Altmann, Simone; Muino, Jose M.; Lortzing, Vivien; Brandt, Ronny; Himmelbach, Axel; Altschmied, Lothar; Hilker, Monika
Abstract: Plant responses to insect egg depositions are known to shape subsequent defensive responses to larvae hatching from the eggs. Elm ( Ulmus minor ) leaves, on which elm leaf beetles laid their eggs, mount a more efficient defence against larvae hatching from the eggs. However, the molecular mechanisms of this egg‐mediated, improved defence are insufficiently understood and have so far only been studied in annual plants. We analysed the dynamics of transcriptomic changes in larval feeding‐damaged elm leaves with and without prior egg deposition using de novo assembled RNA‐seq data. Compared to egg‐free leaves, egg deposition‐treated leaves showed earlier and/or faster transcriptional regulations, as well as slightly enhanced differential transcriptional regulation after the onset of larval feeding. These early responding transcripts were overrepresented in gene ontology terms associated with post‐translational protein modification, signalling and stress (defence) responses. We found evidence of transcriptional memory in initially egg deposition‐induced transcripts whose differential expression was reset prior to larval hatching, but was more rapidly induced again by subsequent larval feeding. This potential memory effect of prior egg deposition, as well as the earlier/faster and enhanced feeding‐induced differential regulation of transcripts in egg deposition‐treated leaves, may contribute to the egg‐mediated reinforcing effect on the elm's defence against larvae. Hence, our study shows that a plant's experience of a stress‐indicating environmental cue (here: insect eggs) can push the dynamics of the plant's transcriptomic response to subsequent stress (here: larval feeding). Such experience‐mediated acceleration of a stress‐induced plant response may result in improved stress resistance.